Manifestation of anxiety and depression and their association with cardiovascular diseases in the Lithuanian population - Burokienė, Neringa; Karčiauskaitė, Dovilė; Kasiulevičius, Vytautas; Kučinskas, Vaidutis; Kučinskienė, Zita Aušrelė (Acta medica Lituanica, 2014)
Background. Cardiovascular diseases (CVD) continue to be the leading cause of morbidity and mortality in Lithuania. The key modifiable factors identified for CVD prevention include lifestyle and behavior factors (e. g. diet, body weight, physical activity, cigarette smoking), and health risk factors (e. g. hypertension, hypercholesterolemia, etc.), also anxiety and depression are considered as potentially modifiable CVD risk factors as well. The aim of this study was to evaluate the association between psychosocial stress, manifested as anxiety and depression, and CVD. Material and methods. 317 individuals (155 men and 162 women) aged 40–85 years were randomly selected from primary care centers in 20 cities of Lithuania. Individuals were interviewed using the validated questionnaire comprising nutritional habits, family history and lifestyle factors. Psychosocial stress was evaluated using the HAD scale. Serum concentrations of cholesterol, HDL-Ch, LDL-Ch, triglycerides were measured. Results. In 103 individuals (32.5%) the symptoms of clinical anxiety were found (HAD score was 8 points and above according to the anxiety scale). 43 individuals (13.6%) had symptoms of clinical depression (HAD score reached 8 points and above according to the depression scale). The median of depression symptoms was significantly different between men and women (p